Public sector physiotherapists' organisation and profile: Implications for intensive care service - Farhana Karachi; Rik Gosselink; Susan Hanekom (AOSIS, 2023)
Background: Physiotherapists are essential in the management of hospitalised patients. The way in which a physiotherapy service is offered in intensive care units (ICUs) can affect ICU patient outcomes. Objectives: To provide a clear picture of the organisation and structure of physiotherapy departments, the number and types of ICUs requiring physiotherapy services and the profile of physiotherapists working in South African public-sector central, regional and tertiary hospitals that house Level I-IV ICUs. Method: Cross-sectional survey design using SurveyMonkey, analysed descriptively. Results: One hundred and seventy units (the majority Level I, functioning as mixed [37%, n = 58] and neonatal [22%, n = 37] units) are serviced by 66 physiotherapy departments. The majority of physiotherapists (61.5%, n = 265) were younger than 30 years, had a bachelor's degree (95.1%, n = 408) and were employed in production Level I and community service posts (51%, n = 217) with a physiotherapy-to-hospital-bed ratio of 1:69. Conclusion: Insight into the organisational structure of physiotherapy departments and physiotherapists working in public-sector hospitals with ICU facilities in South Africa was provided. It is evident that physiotherapists employed within this sector are young and early in their career development. The large number of ICUs functioning within these hospitals and high bed-to-physiotherapist ratio is concerning, highlighting the high burden of care within this sector and the possible effect on physiotherapy services in the ICUs. Clinical implications: A high burden of care is placed on public-sector hospital-based physiotherapists. The number of senior-level posts within this sector raises concern. It is not clear how the current staffing levels, physiotherapist profile and structure of hospital-based physiotherapy departments affect patient outcomes.